Media and cultural representation: The symbolic appropriation of identity in West African Screen Media - (:unkn) unknown (My University, 2021)
This article explores the portrayal of cultural identity in West African screen media, especially through television, cinema and visual advertising. It is exclusively an exploratory research which demonstrates that African cultural identity is essentially linked to its language, art, music, sculpture, as well as the use of local symbols. Hence, this studywhich applies in essence a qualitative research designis conducted in order to better understand the strategy of cultural depiction on West African media screens. As a result, the main objective is to demonstrate that national televisions and cinema really promote cultural identity in West Africa via visual symbolism. Consequently, the current study goes beyond the field of culture and identity to include the multidisciplinary domain of semiotics and visual communication. In fact, the investigations help to clearly understand how cultural identity can be delicately portrayed through the means of visual communication media. Therefore, while this study tends to comprehend the portrayal of cultural identity on West African media screens (Cinema and TV), the research attempts to establish a nexus between culture and globalization before discussing respectively the notions of local languages and identity, as well as the appropriation of cultural symbols via West African TV, cinema and advertising. Also, taking into account the cultural and linguistic diversities through a concrete case study, the analysis focuses specifically on three West African countries (Ghana, Burkina Faso and Mali); which TV sets are well-designed with visual symbols to reflect local identities.
Keywords: African Research